The Effect of Service Quality on Consumer Satisfaction in Creating Reuse Intention of Personal Shopper Services - Jessica Valentina Prawira; Helena Sidharta (Universitas Ciputra Surabaya, 2021)
The purpose of this research is to find out the effect of service quality on consumer satisfaction in creating reuse intention of personal shopper service. The method that is used isquantitative research method. The sample collection technique uses purposive sampling technique with the total sample of 65 respondents who are the consumers that have ever used personal shopper service at least once. Data collection technique is carried out by distributing questionnairesby using Likert Scale as its measurement instrument. The data is analyzed using multivariate technique, that is, Structural Equation Modeling Partial Least Square (SEM-PLS) to analyze the relationship among variables. The result of this research indicates that service quality has the effectsignificantly and positive on consumer satisfaction, consumer satisfaction has the effectsignificantly and positive on reuse intention, service quality does not affect significantly on reuse intention, and service quality has the effect significantly and positive on reuse intention through consumer satisfaction as mediating variable.Keywords: Service Quality, Consumer Satisfaction, Reuse Intention, Personal Shopper Service.